El dengue, ¿un problema para quién? - Ocampo Mallou, Carolina (2020)
Dengue is a recurrent public health problem that affects the American continent. Recent records indicate a historical raise in number of cases in South America, particularly, in Brazil, Paraguay and Bolivia. Correspondingly, in Argentina, outbreaks have occurred almost all years except 2001 and 2005 since 1998. Furthermore, in 2009, 2016 and 2020 the epidemics reached almost half of the country. Therefore, dengue appears to be configured as a disease that cannot be prevented or controlled. As a consequence, our initial aim is to find and examine the meanings about the dengue problem that circulate among health agents and neighbors in a locality in the province of Buenos Aires. We conducted in-depth interviews to health local agents of different status in two health centers and participant observations in local trainings to agents between December and February 2019. According to our findings dengue does not seem to be a problem for the neighbors nor for some of the interviewed health agents. Mosquito bitings and some health problems are the subjects of concern. The preventive measures associated with container treatment are limitted by the multiple meanings and uses that people give to containers. Furthermore, we find that fumigations have many meanings. They appear as the only possible solution and, on the contrary, as a tool of political legitimacy. Similarly, the liability problem is discussed in the interviews with the health workers. In general, we can say that this study supports what is stated in other researches regarding the presence of fractures between the ideals of locality programs and the people’s daily life.